Cisto de colédoco em criança - Artur Guimarães Filho; Simone Alves Frazão de Souza; Vicente Pontes Carvalho (Revista do Colégio Brasileiro de Cirurgiões)
We report the case of a one-year and two-months-old child with a choledochal cyst tYpe I of Alonso-Lej and Todani's classification , diagnosed through abdominal ultrasound. The surgical treatment was cholecistectomy and choledochal cyst excision with Roux-in-Y hepatic- jejunostomy. Minor complications were observed during early postoperative recovery. Long-term flow-up has been uneventiful, with overall improvement.